Determinação experimental de parâmetros de interação e aplicação na simulação CFD-DEM de leito de jorro - Borges, Laira Pinto (Universidade Federal de São Carlos, 2020)
Spouted beds feature the intense mixture of solids, which favors the mechanisms of heat and mass transfer. The understanding of these phenomena is associated with the difficult to obtain details of fluid dynamics by the experimental route, as the measurements can be instrusive, causing changes in the results. Computational fluid dynamics (CFD) proved to be able to assist in this aspect, spreading in the study of spouted beds. With the advance in the processing capacity of computers, there is an expansion in the use of the coupling between CFD and the Discrete Element Method (DEM), known as CFD-DEM. The CFD-DEM is a tool with a high application potential, since it allows to study the phenomena in the particle scale. However, its use depends on the interaction parameters (restitution coefficient, rolling friction coefficient, static friction coefficient) to the model, whose correct definition is directly linked to the quality of the simulated response. Thus, the objective of this work was to obtain the interaction parameters between acrylonitrile butadiene styrene (ABS) spheres, and these with acrylic spheres, through direct measurement, and application in CFD-DEM simulations of a 3D conical spout bed. To validate the simulations, experimental fluid-dynamic curves of three ABS masses were obtained: 400 g, 300 g and 200 g, in a spout bed constructed of acrylic, with a cylinder diameter of 142 mm. Subsequently, simulations were performed using the Two Fluids Model (TFM) to compare the Lagrangean and Eulerian approaches for describing the solid phase. The experimental fluid dynamic curves are consistent with the literature, with minimum spouting velocity 14.8, 13.2, and 11.8 m / s for the masses of 400 g, 300 g and 200 g respectively. Subsequently, simulations were performed using the Two Fluids Model (TFM) to compare the Lagrangean and Eulerian approaches for describing the solid phase. The experimental fluid-dynamic curves are consistent with the literature, with minimum spouting velocities of 14.8, 13.2, and 11.8 m / s for the masses of 400 g, 300 g and 200 g respectively. The curves obtained with CFD-DEM showed a behavior close to the experimental one, indicating the reliability of the interaction parameters obtained experimentally. The minimum spouting velocities were 14.7, 12.3 and 9.1 m / s for the masses of 400, 300 and 200 g of solids, respectively. The largest deviation was obtained for the 200 g mass, being approximately 20.5%. The curves obtained from the TFM do not show the same experimental behavior, with minimum spouting velocity of 7.1 and 6.2 m / s for the masses of 400 and 300 g respectively. Thus, the CFD-DEM simulations best represented the studied system, indicating the potential of the tool for application in the computational simulation of spouted beds.
Experimental determination of interaction parameters and application in the spouted bed CFD-DEM simulation
Keywords: Leito de jorro; Fluidodinâmica computacional; Método dos elementos discretos; Lagrangeano; Acrilonitrila Butadieno Estireno; Spouted bed; Computational fluid dynamics; Acrylonitrile Butadiene Styrene; CFD DEM; ABS; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA